(untitled) (Humanis, 2026)
This study discusses the dynamics of the Ikawangi association as a regional association in the period 2009 to 2018. Some of the issues that will be discussed in this study are (1) How the history of Ikawangi Dewata Balo (2) How the development of Ikawangi Dewata in the period 2009 to 2018, and (3) What are the implications of Ikawangi Dewata for Banyuwangi people in Bali and non-Banyuwangi societies. This research is a historical research. The approach used in the study is social history. The historical theory used is five elements of historical theory initiated by Ida Bagus Sidemen: historical understanding, historical explanation, historical objectivity, historical causation and historical determinism. The results of the study revealed the origin and chronology of the establishment of Ikawangi as a regional based association in Denpasar, Bali. Ikawangi has four branches in various regions in Bali and has a very influential presence on Ikawangi members, the Denpasar commmunity and other migrants.